TcTASV-C, a Protein Family in Trypanosoma cruzi that Is Predominantly Trypomastigote-Stage Specific and Secreted to the Medium - Bernabo, Guillermo (2013)
Among the several multigene families codified by the genome of  T. cruzi, the TcTASV family was the latest discovered. The TcTASV (Trypomastigote, Alanine, Serine, Valine) family is composed by ~40 members, with conserved carboxi- and amino-termini but with a variable central core. According to the length and sequence of the central region the family is split into 3 sub-families. The TcTASV family is conserved in the genomes of  ?at least- lineages I and VI and has no orthologues in other trypanosomatids. In the present work we focus on the study of the  TcTASV-C subfamily,  composed by 13 genes in CL Brener strain. We determined that TcTASV-C is preferentially expressed in trypomastigotes, but it is not a major component of the parasite. Both immunoflourescence and flow cytometry experiments indicated that TcTASV-C has a clonal expression, i.e. it is not expressed by all the parasites of a certain population at the same time. Besides, we determined that TcTASV-C is phosphorylated and glycosylated. TASV-C is attached to the parasite surface by a GPI anchor and is also shed spontaneously into the medium. About 30% of sera from infected hosts reacted with TcTASV-C, confirming its exposition to the immune system. Its superficial localization and secretory nature suggest a possible role in host-parasite interactions.